Higher Education in Persons with Disabilities: Statistical Analysis - Arzhanykh E.V (Moscow State University of Psychology and Education, 2017)
The paper presents statistical research data on teaching/learning in individuals with disabilities enrolled in higher education programmes. The analysis is based on the information drawn from a statistical form VPO-1 "Information on educational organization offering bachelor's, master's and specialist programmes in higher education". The following indicators were analysed: the dynamics of the number of students with disabilities studying at universities; distribution of students according to the level of higher education and the type of their disability; distribution of students according to the chosen profession; and the data collected in the Russian regions. The paper concludes that even though the available statistical data do not allow for a full complex exploration into the subject of higher education in students with disabilities, the scope of the accessible information is reasonably wide.